EFL Students’ Problems and Strategies in TOEFL Test - Ali, Sri Widyarti (LETS: Journal of Linguistics and English Teaching Studies, 2023)
This study aims to investigate the students’ problems and strategies in TOEFL test. The research participants are English Department students who have finished taking the TOEFL test. This research was conducted using qualitative methods, by collecting the data through interviews. The results of this study revealed that in the listening section, participants had difficulty comprehending the words spoken orally by the speakers due to a lack of vocabulary mastery and their inability to comprehend the speakers' pronunciation. They applied several strategies to deal with this listening test, such as attempting to remain focused on listening and capturing as much detailed information as possible during the conversations. The participants also encountered difficulties in the structure and written expression section due to a lack of English grammar mastery, which caused them to answer questions incorrectly, particularly on questions about tenses, parallelism, sentence structure, and word classes. Their general strategy was to practice answering questions on the structure and written expression before taking the actual test. Recognizing the forms and characteristics of TOEFL questions was essential to minimize errors and save time. Meanwhile, in the reading test section, the participants' biggest issue was a lack of vocabulary mastery, which caused them to struggle to comprehend the passages. Thus, their strategy involved employing skimming and scanning techniques while attempting to grasp the text's main idea in order to comprehend the text's content as a whole.